(untitled) ("Conference on Universal Science Research 2023", 2023)
The era of globalization requires the efficient use of technologies to cope with the modern world and its features. Without technology, no nation can think about take off to development. In the business world development means economic growth and running towards its peak. This peak is attainable only after the appropriate use of unique technologies. Technology saves time and mobilizes the economy. Electronic commerce is rapidly growing as an impressive manifestation of globalization. The rapid expansion of e-commerce is a major opportunity for local and international trade development of LDCs including Bangladesh. This study concentrates only on the regulatory framework of e-commerce.